International protection of the environment - Hans-Dietrich Genscher (Intereconomics, 1971)
Environment policy is a crucial part of social policy. The problems involved can be solved only if all act in unison and in close international coordination. A progressive environment policy must comprise all the planning and defensive measures required to safeguard the environment.
Keywords: 330; Social Policy